Oxidative Stress : Environmental Induction and Dietary Antioxidants. - Banga, Jaspreet (Delve Publishing, 2019)
And ProspectiveAcknowledgments; References; Chapter 6 Mechanism of Oxidative Stress in Neurodegeneration; Abstract; Introduction; What is Oxidative Stress?; Box 1: ROS Producers in Mammalian Brain; Box 2: The Antioxidant System; Acknowledgment; References; Chapter 7 Oxidative Stress in Aging Brain: Nutritional and Pharmacological Interventions for Neurodegenerative Disorders; Chapter 8 Oxidative Stress in Neurodegenerative Diseases: Mechanisms and Therapeutic Perspectives; Abstract; Introduction; Molecular Mechanisms; Looking For New Neuroprotectants